A case study from Guyana of adapting engaged research design to promote 'fairness in knowing'. (17th May 2022) - Holliman, Richard; Marino, Alessandra; Grand, Ann; Berardi, Andrea; Mistry, Jay; Jafferally, Deirdre; Thomas, Raquel; Roberts, Grace; Marcus, Carol-Ann; Roopsind, Indranee; Roberts, Anthony
Abstract : page_1 other In this paper, we have combined ideas drawn from philosophy (epistemic injustice), critical theory (epistemicide) and practical approaches (engaged research design) with Indigenous knowledge to promote 'fairness in knowing' in a project called DETECT (Integrated Space T echnology Ve ctor C ont rol for Enhancing community health and resilience against escalating climatic disruptions), an early warning system to support communities in identifying mosquito breeding sites using satellite, drone and ground-sensing technologies. DETECT used engaged research design to inform pre-award planning. We document how the project team, comprising Indigenous and other researchers, page_2 other re-imagined the plans in the light of the COVID-19 pandemic to allow project participants to meet safely and equitably, and reflect on some of the key challenges in engaging across borders and cultures in the context of rapidly changing conditions characterised by vulnerability, risk, complexity and uncertainty.